2022
DOI: 10.1029/2022wr033155
|View full text |Cite
|
Sign up to set email alerts
|

Dual State‐Parameter Assimilation of SAR‐Derived Wet Surface Ratio for Improving Fluvial Flood Reanalysis

Abstract: Flooding is one of the most devastating natural hazards to which our society worldwide must adapt, especially as its severity and occurrence tend to increase with climate changes. This research work focuses on the assimilation of two‐dimensional (2D) flood observations derived from remote‐sensing images acquired during overflowing events. To do so, the resulting binary wet/dry maps are expressed in terms of wet surface ratios (WSR) over a number of floodplain subdomains. This ratio is assimilated jointly with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…It is worth-noting that the corrections of the hydraulic state in the floodplain (𝛿𝐻 [1:5] ) are only performed at the assimilation window in which WSR observations are present. A full study including real flood events can be found in [11].…”
Section: Truth and Observation Generationmentioning
confidence: 99%
“…It is worth-noting that the corrections of the hydraulic state in the floodplain (𝛿𝐻 [1:5] ) are only performed at the assimilation window in which WSR observations are present. A full study including real flood events can be found in [11].…”
Section: Truth and Observation Generationmentioning
confidence: 99%